Performance Analysis Using the Balanced Scorecard Approach at Dr. Soedarso Regional General Hospital West Kalimantan Province - Utami, Tramilia Salsabila; Ryanto, Fuad Ramdhan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study analyzes the performance of Dr. Soedarso Regional General Hospital in West Kalimantan Province during the period 2021–2024 using the Balanced Scorecard approach. Measurements were conducted from the perspectives of finance, customers, internal business processes, and learning and growth. The results show a decrease in ROI from 12% to 9%, but cost efficiency remained relatively stable at around 82–84%. Patient acquisition experienced fluctuations, with a decline in 2022 and a subsequent increase in the following year. Overall customer satisfaction levels were categorized as good. Internal business process indicators such as BOR, ALOS, TOI, BTO, NDR, and GDR were within the established standard ranges. Employee productivity was recorded at 1,659,948 per day with an employee retention rate of 91%. Employee satisfaction is generally rated as good, although there are notes on career progression and room for suggestion submission. This data provides an overview of the hospital's performance from various perspectives in accordance with the Balanced Scorecard methodology.